2009
DOI: 10.1007/s00005-009-0011-3
|View full text |Cite
|
Sign up to set email alerts
|

The roles of the RAG1 and RAG2 “non-core” regions in V(D)J recombination and lymphocyte development

Abstract: The enormous repertoire of the vertebrate specific immune system relies on the rearrangement of discrete gene segments into intact antigen receptor genes during the early stages of B-and T-cell development. This V(D)J recombination is initiated by a lymphoid-specific recombinase comprising the RAG1 and RAG2 proteins, which introduces double-strand breaks in the DNA adjacent to the coding segments. Much of the biochemical research into V(D)J recombination has focused on truncated or "core" fragments of RAG1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
61
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 85 publications
0
61
0
Order By: Relevance
“…Rare experiments describing full-length RAG1/2 complexes have reported very low enzyme activities, making conclusions very difficult (12,37). However, recent studies have revealed that noncore regions of RAG proteins have important roles in regulating V(D)J recombination (20). The PHD finger of RAG2 located in the noncore region directly interacts with histone H3, with trimethylation on Lys4 (24,25), and this interaction stimulates RAG cleavage activity, thereby resulting in improved efficiencies of V(D)J recombination (36).…”
Section: Resultsmentioning
confidence: 99%
“…Rare experiments describing full-length RAG1/2 complexes have reported very low enzyme activities, making conclusions very difficult (12,37). However, recent studies have revealed that noncore regions of RAG proteins have important roles in regulating V(D)J recombination (20). The PHD finger of RAG2 located in the noncore region directly interacts with histone H3, with trimethylation on Lys4 (24,25), and this interaction stimulates RAG cleavage activity, thereby resulting in improved efficiencies of V(D)J recombination (36).…”
Section: Resultsmentioning
confidence: 99%
“…However, there is some indirect evidence of a similar mechanism in mammalian somatic cells when transduced with lentiviral vectors. In fact, reduced expression of the introduced transgene was observed during differentiation in a murine model and silencing was found to be the result of DNA methylation of the promoter of the lentivirus driven August 12, 2015|Volume 4|Issue 3| WJV|www.wjgnet.com 229 [229] , SET7 (mono) [230] , MLL [231] , SMYD2 [232] LSD1 (mono and di) [233] , JARID1A/ KDM5A JARID1B/ KDM5B (di and tri) [234] CHD1 [235] , RAG2 [236] , TAF3 [237] , BPTF [238] , BHC80 [239] , ING FAMILY [240] , PYGO2 [241] [ [244] SIRT6 [245] BRD4 [246] [247]…”
Section: H3k27me3 or H3k9me3mentioning
confidence: 99%
“…Since their discovery, the full-length RAG1 and RAG2 proteins have proven difficult to isolate and study in vitro (1). However, core domains (referred to as RAG1c and RAG2c) have been identified by removing a large region from the N terminus of RAG1 (which includes an E3 ubiquitin ligase domain) and a large region from the C terminus of RAG2 (which includes a plant homeodomain) (3,4). These core proteins have been shown to tetramerize to form RAG1/2c, which retains RSS binding, nicking, and hairpin formation activities (5).…”
mentioning
confidence: 99%